Analysis of Principals’ Decision-Making: A Literature Study - Hardianto Hardianto; Zulkifli Zulkifli; Hidayat Hidayat (STAI Hubbulwathan Duri, 2021)
This research was conducted to analyze the decision making by the principal. The analysis is carried out on the stages of decision making, influencing variables and factors, so that decision making is better. Effective decision making will make the school able to realize its vision and goals. This research uses the literature study method. The main source of research data is articles on school principals' decision-making obtained from Google Scholar. The technique of data collection is done by the method of documentation. The results showed that the principal has carried out the decision-making process by following six decision-making steps: problem identification, gathering information, developing alternative solutions, choosing the best alternative, implementing alternatives, and evaluating decisions. There are five variables that influence decision making by the principal. The five variables are self-efficacy, administration knowledge, management information system, emotional quotient and personality. Decision-making by the principal will be more effective by involving teachers and education staff.